Reasons for Early Child Marriages in Pakistan: A Comparative Analysis of its Causes and Comparison with Other Countries - Hafiz Muhammad Haseeb Ulla; Hafiz Abdul Rehman Saleem; Manahil Saleem; Sara Saeed; Bilal Ahmad (Research Journal of Psychology, 2025)
Child Marriage is a complex phenomenon which is multiple and grave violations of rights of children depriving and limiting their opportunities for full realization of their potentials. The practice also violates the human rights of boys and girls and perpetuates the cycle of poverty. The male–female ratio among practice is not equal, the consequences are heavier on a girl than a boy. Child marriage obstructs the realization of the Sustainable Development Goals 1, 3, 4, 5, 8 and 10. Pakistan's legislation and implementation of the laws to prohibit child marriages is complicated and must be addressed according to the provincial cultural background. Evidence based research is needed to support the legislation and to help develop responses which are specific, targeted and address the right drivers to child marriages to ensure that the policy and legislation can be informative for policy makers and civil society actors to implement adequate strategies. This research’s main discussion is the causes and factors contributing the child marriages in Pakistan. The research also put forwards various recommendations to end child marriages and suggests some important factors, as per needs and requirements of the community which can help in delaying child marriages.